Thermal and Electrical Transport Properties of o-Substituted Polyanilines Encapsulated with CuO Nanoparticles - Suganthi, R.; Mary, S. Jhancy (Asian Journal of Chemistry, 2019)
Fabrication of substituted polyaniline nanocomposites with CuO results in hybrid materials with enhanced synergistic properties. Hence poly(2-chloroaniline)-composite-CuO, poly(2-chloroaniline)-composite-CuO/SDS, poly(2-methoxyaniline)-composite-CuO/SDS and poly(2-methylaniline)-composite-CuO/SDS nanocomposites were prepared chemically by in situ oxidative polymerization method. Characterization by a number of techniques such as FTIR, NMR and UV-visible spectroscopic methods, XRD and TEM are presented. The substituted polymers exhibited an appreciable interaction with the CuO (5 wt.%) nano fillers. Integral Procedural Decomposition Temperature (IPDT) and Oxidative Index(OI) calculations were done to establish the stability to heat. Thermal stability of the materials follows the trend p2ClAni-CuO-SDS > p2ClAni-CuO> p2MeAni-CuO-SDS> p2OMeAni-CuO-SDS. The electrical conductivities of poly(2-chloroaniline)-composite-CuO and poly(2-chloroaniline)-composite-CuO/SDS measured are 1.46 × 10-7 and 1.59 × 10-7 S cm-1, respectively and the presence of anionic surfactant does not change the electrical conductivity behaviour. The poly(2-methoxyaniline)/CuO-SDS and poly(2-methylaniline)/CuO-SDS exhibit an electrical conductivity of 1.68 × 10-6 and 1.24 × 10-6 S cm-1 respectively. The dielectric constant decreased with increase in frequency in the low frequency region due to electrical relaxation process. At low frequency there was a strong frequency dispersion of permittivity and above 2.5 Hz a frequency independent behavior was noted.